2012
DOI: 10.1103/physrevb.86.134514
|View full text |Cite
|
Sign up to set email alerts
|

Pair-density wave states through spin-orbit coupling in multilayer superconductors

Abstract: Spin singlet superconductors with quasi-two dimensional multilayer structure are studied in high magnetic fields. Specifically we concentrate on bi-and tri-layer systems whose layers by symmetry are subject Rashba-type spin-orbit coupling. The combination of magnetic field and spin-orbit coupling leads to a first order phase transition between different states of layer-dependent superconducting order parameters upon rising the magnetic field. In this context we distinguish the low-field Bardeen-Cooper-Schrieff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
141
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 92 publications
(151 citation statements)
references
References 21 publications
9
141
1
Order By: Relevance
“…Although CeCoIn 5 and high-T c cuprates are believed to be a d-wave superconductor and would have a small odd-parity component admixed with the local non-centrosymmetricity, the features found below are independent of the pairing symmetry as long as the spin-singlet pairing is predominant. In fact, we have confirmed that the model for dwave superconductivity gives the qualitatively same results [8]. Hence, for the sake of numerical accuracy, we restrict ourselves to the simpler s-wave state.…”
Section: Modelsupporting
confidence: 55%
See 3 more Smart Citations
“…Although CeCoIn 5 and high-T c cuprates are believed to be a d-wave superconductor and would have a small odd-parity component admixed with the local non-centrosymmetricity, the features found below are independent of the pairing symmetry as long as the spin-singlet pairing is predominant. In fact, we have confirmed that the model for dwave superconductivity gives the qualitatively same results [8]. Hence, for the sake of numerical accuracy, we restrict ourselves to the simpler s-wave state.…”
Section: Modelsupporting
confidence: 55%
“…Interestingly, the order parameter configuration with a sign change, (∆ 1 , ∆ 2 ) = (∆, −∆), becomes more stable at high magnetic fields, as shown in Ref. 8. This state is called the pair-density wave (PDW) state in Fig.…”
Section: Bilayer Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…A sublattice-dependent antisymmetric spin-orbit coupling (ASOC) arises from the local parity violation in crystal structures. Previous studies of superconductivity in multilayers, [1][2][3][4] magnetic quadrupole order in zigzag chains, 5,6) toroidal order in a honeycomb lattice, 7,8) and electric octupole (EO) order in bilayer systems 9) have revealed exotic quantum states of matter induced by the ASOC. On the basis of the generalized multipole expansion, 10) some of them are classified into odd-parity multipole states beyond the paradigm of even-parity multipole order studied in d-and f -electron systems.…”
Section: Introductionmentioning
confidence: 99%